Health‐related quality of life in adults with osteogenesis imperfecta. Issue 6 (22nd February 2021) - Murali, Chaya N.; Slater, Brady; Musaad, Salma; Cuthbertson, David; Nguyen, Dianne; Turner, Alicia; Azamian, Mahshid; Tosi, Laura; Rauch, Frank; Sutton, V. Reid; Lee, Brendan; ,; et al.
Abstract: Patient‐reported outcome measures (PROMs) are increasingly utilized as endpoints in clinical trials. The Short Form Health Survey‐12 (SF‐12v2) is a generic PROM for adults. We sought to evaluate the validity of SF‐12v2 in adults with osteogenesis imperfecta (OI). Physical and mental health‐related quality of life (HRQoL) were assessed in a large cohort of adults in a multicenter, observational, natural history study. Physical HRQoL scores were correlated with the Gillette Functional Assessment Questionnaire (GFAQ). We calculated sample sizes required in clinical trials with crossover and parallel‐group designs to detect clinically meaningful changes in physical HRQoL. Three hundred and two adults with OI types I, III, and IV were enrolled. Physical HRQoL scores in the study population were lower than population norms. Physical HRQoL scores moderately correlated with GFAQ for OI types I and IV. We found no correlations between mental and physical HRQoL. From a clinical trial readiness perspective, we show that SF‐12v2 reliably measures physical function in adults with OI and can be utilized in crossover trials to detect meaningful physical HRQoL changes with small sample sizes. This study shows that SF‐12v2 can be used to measure changes in physical HRQoL in response to interventions in OI. Abstract :